Corrigendum to "The knockdown of the maternal estrogen receptor 2a (esr2a) mRNA affects embryo transcript contents and larval development in zebrafish" [Gen. Comp. Endocrinol. 172 (2011) 120-129] (DOI:10.1016/j.ygcen.2010.12.020) - Celeghin A. (2014)
[No abstract available]